Associations between mealtime anxiety and food intake in anorexia nervosa. Issue 9 (29th July 2021) - Lloyd, E. Caitlin; Powell, Chanel; Schebendach, Janet; Walsh, B. Timothy; Posner, Jonathan; Steinglass, Joanna E.
Abstract: Objective: A salient disturbance in anorexia nervosa (AN) is the persistent restriction of food intake. Eating behavior in AN is thought to be influenced by anxiety. The current study probed associations between mealtime anxiety and food intake among individuals with AN and healthy comparison individuals (HC). Method: Data were combined across three studies (total of 92 AN and 78 HC) for secondary data analysis. Participants completed a multiitem laboratory buffet meal and visual analogue scale assessments of pre‐meal and post‐meal anxiety. Linear regression models assessed the association between mealtime anxiety and calorie and fat intake at the meal, and whether associations differed by diagnostic group. Results: Among individuals with AN, pre‐meal anxiety was significantly associated with reduced calorie intake and reduced consumption of calories from fat at the meal; these associations were not observed among HC. There was no evidence for an association between calorie/fat intake at the meal and post‐meal anxiety in either group. Discussion: Treatments that target mealtime anxiety may improve eating and nourishment among individuals with AN. Interventions like exposure therapy that provide skills in overcoming mealtime anxiety might be enhanced by informing patients that post‐meal anxiety is not related to intake.